Counteracting Bacterial Motility: A Promising Strategy to Narrow Listeria monocytogenes Biofilm in Food Processing Industry - Doghri, Ibtissem; Cherifi, Tamazight; Goetz, Coralie; Malouin, François; Jacques, Mario; Fravalo, Philippe (Frontiers in Microbiology, 2021)
Listeriosis is a severe disease caused by Listeria monocytogenes, a Gram-positive, foodborne pathogen. L. monocytogenes is often associated with processed food as it can form biofilms that represent a source of contamination at all stages of the manufacturing chain. The control and prevention of biofilms in food-processing plants are of utmost importance. This study explores the efficacy of prospect molecules for counteracting bacterial mechanisms leading to biofilm formation. The compounds included the phytomolecule tomatidine, zinc chloride (ZnCl2), ethylenediaminetetraacetic acid (EDTA), and a more complexed mixture of bacterial compounds from coagulase-negative staphylococci (CNS exoproducts). Significant inhibition of L. monocytogenes biofilm formation was evidenced using a microfluidic system and confocal microscopic analyses. Active molecules were effective at an early stage of biofilm development (adhesion phase) but failed to disperse mature biofilms of L. monocytogenes. Prevention of surface attachment was associated with a disruption of bacterial motility. Overall, results highlighted the critical role of motility in biofilm formation and allow to consider flagellum-mediated motility as a promising molecular target in control strategies against L. monocytogenes in food processing environments.